Changing Profile of Indian Banking System and Modern Technology: Challenges & Issues: The evolution and challenges of the Indian banking system (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A commercial bank is a financial broker in the Indian banking system that takes deposits of money from the government and loans them to benefit. A post office can take deposits but can't be considered a bank backing because it doesn't do a bank's other important feature, i.e. lending capital. Similarly, some other entities including Unit Trust of India (UTI), however cannot be termed banks because they do not allow checkable deposits. They are not banking finance firms1.